Protection and maintenance of Protestant Churches in Skoki in the first half of the 18th Century, as an example of investment in the well-being of residents - Lepalczyk , Anna (Studia Historiae Oeconomicae, 2025)
In 1717, the First Polish Republic (the Polish-Lithuanian Commonwealth) introduced a constitution that limited the freedom of worship for dissenting faiths and allowed for the closure of non-Catholic churches. The new law has also become a problem for the Wielkopolska’s non-Catholic communities. It forced them to make additional investments in legal protection and maintenance of their congregations. The purpose of this article is to show how important it was to maintain the possibility of fulfilling the spiritual needs of non-Catholic inhabitants of the Commonwealth for the balanced development of local societies. The problem was discussed on the example of the private town of Skoki, inhabited by the Evangelical Reformed and Evangelical Augsburg communities. The article used financial sources used in the court process of the local congregations in 1720 and sources describing the fight against the effects of the fire in 1740. The main conclusions of their analysis indicate that investments were made collectively and had a supra-state dimension. The funds raised through donations and local and national collections were managed by influential people with personal assets, and then transparently accounted for. The financial effort made despite legal obstacles allowed for maintaining the social position of communities, balance between denominations, and finally, the well-being of residents, which translated into economic development of the locality.